ANALISIS KESIAPAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Faiza Nur Andina Andina; Nataria Wahyuning Subayani; Ismail Marzuki (JS (JURNAL SEKOLAH), 2023)
Abstract: This study aims to analyze teacher readiness in implementing the independent curriculum in class V UPT SDN 73 Gresik in terms of lesson planning, learning implementation and learning assessment. This research uses a qualitative descriptive approach. This research was conducted at UPT SDN 73 Gresik, in Ngering Hamlet to be precise. Sukoanyar, Cerme District, Gresik Regency with 5 subjects including the principal, class V teacher, PJOK class V subject teacher, PAI subject teacher class V and English subject teacher class V. The data collection technique used in this study was Interview, Observation and Documentation. The analysis of this research uses an interactive model or the Miles and Huberman Model. Based on the results of the analysis that has been carried out, the results of the analysis of teacher readiness in implementing the independent curriculum in class V UPT SDN 73 Gresik which are reviewed in terms of lesson planning show that all V teachers have fulfilled the readiness and availability contained in the learning planning aspect which includes the formulation of objectives learning (TP), the preparation of learning objectives flow (ATP) and the preparation of teaching modules. The readiness of teachers in implementing the independent curriculum in grade V, which was reviewed from the point of view of implementing learning, showed that 2 out of 4 teachers teaching in class V had met the readiness and availability contained in the aspects of implementing learning. The readiness of teachers in implementing the independent curriculum in grade V which was reviewed in terms of learning assessment showed that all teachers in grade V had fulfilled the readiness and availability contained in the learning assessment aspects which included initial assessments, formative assessments and summative assessments.Keyword: Teacher Readiness, Implementation of Independent Curriculum.Abstrak: Penelitian ini bertujuan untuk menganalisis kesiapan guru dalam implementasi kurikulum merdeka di kelas V UPT SDN 73 Gresik yang di tinjau dari segi perencanaan pembelajaran, pelaksanaan pembelajaran dan asesmen pembelajaran. Penelitian ini menggunakan metode pendekatan deskriptif kualitatif. Penelitian ini dilaksanakan di UPT SDN 73 Gresik, tepatnya di Dusun Ngering. Sukoanyar Kecamatan Cerme Kabupaten Gresik dengan subjek sebanyak 5 orang diantaranya Bapak kepala sekolah, guru kelas V, guru mata pelajaran PJOK kelas V, guru mata pelajaran PAI kelas V dan guru mata pelajaran bahasa Inggris kelas V. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah Wawancara, Observasi dan Dokumentasi. Analisis penelitian ini menggunakan model interaktif atau Model Miles dan Hubermen. Berdasarkan hasil analisis yang telah dilakukan bahwa Kesiapan guru dalam implementasi kurikulum merdeka di kelas V UPT SDN 73 Gresik yang di tinjau dari segi perencanaan pembelajaran menunjukkan bahwa seluruh guru V telah memenuhi kesiapan dan ketersediaan yang terdapat dalam aspek perencanaan pembelajaran yang meliputi perumusan tujuan pembelajaran (TP), penyusunan alur tujuan pembelajaran (ATP) dan penyusunan modul ajar. Kesiapan guru dalam implementasi kurikulum merdeka di kelas V yang di tinjau dari segi pelaksanaan pembelajaran menunjukkan hasil bahwa 2 dari 4 guru yang mengajar di kelas V telah memenuhi kesiapan dan ketersediaan yang terdapat dalam aspek pelaksanaan pembelajaran. Kesiapan guru dalam implementasi kurikulum merdeka di kelas V di tinjau dari segi asesmen pembelajaran menunjukkan hasil bahwa seluruh guru di kelas V telah memenuhi kesiapan dan ketersediaan yang terdapat dalam aspek asesmen pembelajaran yang meliputi asesmen awal, asesmen formatif dan asesmen sumatif.Kata Kunci: Kesiapan Guru, Implementasi Kurikulum Merdeka